Noncommutative Structures in Mathematics and Physics 2001
DOI: 10.1007/978-94-010-0836-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Locally Anisotropic Supergravity and Gauge Gravity on Noncommutative Spaces

Abstract: We outline the the geometry of locally anisotropic (la) superspaces and la-supergravity. The approach is backgrounded on the method of anholonomic superframes with associated nonlinear connection structure. Following the formalism of enveloping algebras and star product calculus we propose a model of gauge la-gravity on noncommutative spaces. The corresponding Seiberg-Witten maps are established which allow the definition of dynamics for a finite number of gravitational gauge field components on noncommutative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Equation (64) can be integrated in general off-diagonal forms for configurations with D = D and, if necessary, for further restrictions to D | T =0 = ∇. Exact classical and quantum solutions with generalized connections and for nonholonomic configurations have been studied in a series of works [143,144,146,152,153,156,157,161,166,169,180,181]. Recently, such solutions were found for locally anisotropic interactions of gravitational fields and effective matter fields, EYMH systems in GR and string gravity, for nonholonomic quantization of gauge models of gravity etc., see [23,190,198,203,209] and references therein.…”
Section: Eymh Systems On Pseudo Lagrange Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (64) can be integrated in general off-diagonal forms for configurations with D = D and, if necessary, for further restrictions to D | T =0 = ∇. Exact classical and quantum solutions with generalized connections and for nonholonomic configurations have been studied in a series of works [143,144,146,152,153,156,157,161,166,169,180,181]. Recently, such solutions were found for locally anisotropic interactions of gravitational fields and effective matter fields, EYMH systems in GR and string gravity, for nonholonomic quantization of gauge models of gravity etc., see [23,190,198,203,209] and references therein.…”
Section: Eymh Systems On Pseudo Lagrange Spacesmentioning
confidence: 99%
“…It is possible to elaborate a N-adapted Palatini formalism [104], quasi-classical extensions, noncommutative and nonassociative generalizations, deformation quantization, gauge like gravity theories etc., see Refs. [32][33][34]37,38,42,146,147,152,156,157,159,162,167,168,170,179,190,206].…”
Section: Principles and Main Theorems For Modified Field Equations Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Equations ( 64) can be integrated in general off-diagonal forms for configurations with D = D and, if necessary, for further restrictions to D | T =0 = ∇. Exact classical and quantum solutions with generalized connections and for nonholonomic configurations have been studied in a series of works [278,316,280,283,298,303,302,299,308,325,344,345]. Recently, such solutions were found for locally anisotropic interactions of gravitational fields and effective matter fields, EYMH systems in GR and string gravity, for nonholonomic quantization of gauge models of gravity etc., see [355,365,371,376,50] and references therein.…”
Section: Eymh Systems On Pseudo Lagrange Spacesmentioning
confidence: 99%
“…A series of results on MGTs with local anisotropy and Finsler like modifications were reviewed and presented in [299,308,325,333,349]. It was shown that such constructions involve MDRs which can be derived for propagation of point mass classical particles and/or models with quantum variables and (non)commutative relations describing quantum fundamental field interactions [302,303,119,121,122,123,124,321,67,334,343,387,388]. Various classes of locally anisotropic (non) commutative/ associative classical and quantum field and spacetime theories can be described naturally in terms of nonholonomic variables as some models of commutative and/or noncommutative geometries.…”
Section: Introductionmentioning
confidence: 99%